Ordenamiento estratégico del territorio de la parroquia de Zámbiza, del Distrito Metropolitano de Quito: Diseño arquitectónico campus universitario bioclimático agrícola con residencia universitaria en San José de Cocotog - Yépez Tito, Andrea Estefanía (2011)
Quito is the macro centrality, which has microcentralities that have facilities where theexcess of them in the same centrality has created problems of congestion, lack of parking spaces, and other issues affecting the city and its habitants. The GTPD (General Territorial Plan of Development)raises decentralizing and redefining the city limits, a compact city, and the relocation of facilities to suburban areas for further developments. Zambiza is located near the northern center of Quito, and in a few minutes you can connect north with the south of Quito by the Simon Bolívar avenue, but with all these characteristics, Zambiza could not be established, due to, stigma of the garbage that has suffered for years, because of the garbage dump that was located in the entrance of Zambiza,where currently is the transfergarbage station. Moreover, Zambiza has a land designated for agriculture, but its people have missed this opportunity of that fertile lan because of the lack of knowledge and support of the authorities for them. Therefore, has been proposed that Zambiza becomes into a new centrality, equipped with all necessary facilities for future residents and to achieve increase their habitants selves. Creating the master urban lines that define the new center in San José de Cocotog also has been added complementary equipment, such as university education.This equipment is proposed to create a university education that is consistent with the land use, agriculture, so establishing a new agricultura! bioclimatic university campus, which had 4 faculties: Faculty of Agricultura! Sciences, Faculty of Science, Faculty of Forestry and Environment, Faculty of Hotel and Tourism. This institution will be able to disseminate and teach their students the importance of caring for the planet and the problems it has suffered from a lack of awareness, as students carry within them a “green seal” to be future professionals who will form a new green society . VIl The campus design is based on the principies of bioclimatic architecture, which respects the environment and optimizes resources in the best way. The buildings and their distribution born on the principie that shapes a seeding within a plot, with the rows as the main distribution, so that is born of a campus center that is the main square Cocotog connection, and from this center are displayed so that large would walk to connect all the buildings from the main square. The buildings follow these walkways and a proper orientation for the entry of light, wind and views. Also, each building is surrounded by green spaces, gardens and has its separate place and seat of integration between faculties, for the interaction of student.